1967
DOI: 10.1002/hlca.19670500302
|View full text |Cite
|
Sign up to set email alerts
|

Die Enonamin‐Enolimin‐Tautomerie

Abstract: A study of the ultraviolet, infrared, and nuclear magnetic resonance spectra of Δ8,9‐octahydro‐7‐quinolone (7a) and of the corresponding N‐ and O‐ethyl derivatives 8 and 9, respectively, confirms that in cases of potential enonamine‐enolimine tautomerism the enonamine form predominates. This also applies to vinylogous amides capable of intramolecular hydrogen bonding, such as 2‐benzylaminomethylene‐ and 2‐phenylaminomethylene‐cyclohexanone, 10 and 11, respectively. Exeptions are only observed in cases where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

1967
1967
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…Um die fur eine synchrone Fragmentierung notwendigen stereoelektronischen Anforderungen genauer abzuklaren, werden die stereoisomeren 3-Chlorotropane und -nor-73) Der Einfluss sterischer Faktoren sowie das Durchlaufen energiereicher Zwischenstufen bei der Fragmentierung von -Aminoketoximen werden ebenfalls studiert [240]. Die Umlagerung von optisch aktiven Ketoximtosylaten wird von H. P. Fischer untersucht [241].…”
Section: Fig 77unclassified
“…Um die fur eine synchrone Fragmentierung notwendigen stereoelektronischen Anforderungen genauer abzuklaren, werden die stereoisomeren 3-Chlorotropane und -nor-73) Der Einfluss sterischer Faktoren sowie das Durchlaufen energiereicher Zwischenstufen bei der Fragmentierung von -Aminoketoximen werden ebenfalls studiert [240]. Die Umlagerung von optisch aktiven Ketoximtosylaten wird von H. P. Fischer untersucht [241].…”
Section: Fig 77unclassified
“…This form can be stabilized by some structural fragments, such as, for example, aromatic rings. [18] The enaminoketone form (B) is the most stable due to the presence of a strong hydrogen bond and the formation of a pseudo-aromatic ring, which increases the thermodynamic stability of the molecule. [19] A large amount of evidence has been collected using NMR, UV, IR spectroscopy as well as X-ray crystallography which showed that the most of the βenaminones exists in the tautomeric enaminoketone form.…”
Section: Introductionmentioning
confidence: 99%
“…The transition to the enolimine form (C) occurs, as a rule, if there is a significant gain in the conjugation energy of the molecule as a whole (for example, the formation of a pseudo‐aromatic ring). This form can be stabilized by some structural fragments, such as, for example, aromatic rings [18] . The enaminoketone form (B) is the most stable due to the presence of a strong hydrogen bond and the formation of a pseudo‐aromatic ring, which increases the thermodynamic stability of the molecule [19] .…”
Section: Introductionmentioning
confidence: 99%
“…AUS der Chelatform 4w geht hervor, daB die freie Drehbarkeit der Aminogruppe eingeschriinkt ist, die Protonen nicht mehr aquivalent sind und deshalb das Methinproton mit den Protonen der Aminogruppe in cis-trans-Stellung koppelt. Das Signal des trans-standigen Protons erscheint im Spektrum infolge Wasserstoffbrukkenbindung zur Mchstliegenden ringstandigen K e t~g r u p p e~~'~~ 11) …”
unclassified